A WEB-BASED INFORMATION SYSTEM FOR LECTURER'S PERFORMANCE APPRAISAL USING RATING SCALE METHODS - Diovianto Putra Rakhmadani; Faisal Dharma Adhinata (Jurnal Riset Informatika, 2021)
Online learning is widely used by every educational institution during the Covid-19 pandemic. Without face-to-face meetings, lecturers are required to present quality learning with feedback from students. The problem that arises is that EDOM is considered too long in terms of data processing, while lecturers are required to carry out quality teaching at each meeting. If students lose interest in a lecture due to the performance of the lecturer who is unable to make each virtual class attractive, the lecture activity will be ineffective. With the existence of a performance measurement system with the application of gamification that can measure the performance of lecturers at each meeting, lecturers can receive feedback while pursuing rewards or ratings on their performance. This study uses the waterfall model and produces a web-based information system that can be used as evaluation material in improving the quality of online learning.